Malaysian Fertility Transitions: Analyses and Projections of ASFR and TFR by Ethnicity - N. Shair, Syazreen; Y. Yusof, Aida; N. M. Khair, Siti; I. Sharan, Nurul (International Journal of Engineering and Technology, 2019)
This paper presents the study of Malaysian fertility transitions: analyses and projections of age-specific fertility rates (ASFRs) and total fertility rates (TFRs) by ethnicity. In this study, the trends of ASFR and TFR were analysed and compared between ethnic groups, and provided insightful explanation behind the fertility transition over the last six decades from year 1958 to 2015. This paper is the first to adopt the functional data model to estimate fertility rates using Malaysia data. The advantage of the functional model over the mathematical curve approaches is that its ability to account for changes in fertility trends over the years. We use the functional data model to estimate future Malaysian ASFRs and TFRs according to three ethnic groups: Malay, Chinese and Indian. Results show that Malaysian total fertility rates (TFRs) have decreased tremendously from 6.28 children for every woman (aged 15 to 49) in 1958 to 2.23 children in 2015. The forecasts of age-specific fertility rates show that the ages of the highest births gradually change to older age, indicate that the trend of Malaysian women delaying their first birth, will continue to happen in the future. The forecasts of Malaysian TFR show that the TFRs of Chinese and Indian record the lowest low fertility, which is below 1.0 by 2027 and 2030 respectively.Â Â